Increased Cardiovascular Risk in Psoriatic Arthritis: Results From a Case-Control Monocentric Study - Degboé, Yannick; Koch, Richard; Zabraniecki, Laurent; Jamard, Bénédicte; Couture, Guillaume; Ruidavets, Jean Bernard; Ferrieres, Jean; Ruyssen-Witrand, Adeline; Constantin, Arnaud (Frontiers in Medicine, 2022)
Background Psoriatic arthritis (PsA) is associated with increased cardiovascular morbidity and mortality. The aims of our real-life study were to compare the prevalence of cardiovascular risk factors (CVRFs) and cardiovascular events (CVEs) among patients with PsA with a control population, to evaluate the impact of correcting factors in equations that assess cardiovascular risk (CVR) in PsA, and to determine the percentage of patients who reach the LDLc target as indicated by the European guidelines. Methods In this observational cross-sectional monocentric case-control study, we used a standardized procedure to systematically assess patients with PsA aged 25–85 years who met the Classification for Psoriatic Arthritis (CASPAR) criteria. Controls were extracted from the MOnitoring NAtionaL du rISque Artériel (MONALISA) study. We compared the prevalence of CVRFs, CVEs, the CVR, and the percentage of patients reaching recommended LDLc target in both populations. The CVR was first assessed using SCORE and QRISK2 equations. Then, the SCORE equation was corrected by applying a 1.5 multiplication factor, as recommended by EULAR for rheumatoid arthritis (SCORE-PsA), and the QRISK2 was corrected using the “rheumatoid arthritis” item (QRISK2-PsA). Results A total of 207 PsA and 414 controls were included. CVRFs and CVEs were more frequent in the PsA group. After controlling for age and gender, atherothrombotic disease was increased in the PsA population (SCORE p = 0.002, QRISK2 p = 0.001). Using the SCORE-PsA increased the percentage of patients with a high or very high CVR from 39.3 to 45.3% in the PsA group. Similarly, using the QRISK2-PsA increased the percentage of patients with a CVR ≥ 10% from 44.9 to 53.2%. The percentages of patients with PsA with high LDLc in the high and very high CVR groups were not significantly different from controls, despite a trend in favor of patients with PsA. Of the 83 PsA with a QRISK2 ≥ 10%, only 22.9% were treated with statin vs. 35.8% of the 134 controls. The QRISK2-PsA score did not alter these results. Conclusion In real-life, patients with PsA have a higher prevalence of CVRFs, as well as a higher prevalence of CVEs compared to the general population. The CVR is higher in the PsA population than in the controls either using the SCORE and QRISK2 equations or using the corrected SCORE- PsA and QRISK2-PsA equations.